Pajak Pertambahan Nilai Barang dan Jasa Serta Pajak Penjualan Atas Barang Mewah - Al Ramzy; Asnawi Asnawi; Wahyudin Wahyudin; Dini Vientiany (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
A few of the most prominent forms of taxation in Indonesian law are the Value Added Tax (VAT) and the Sales Tax on Luxury Goods (PPnBM). The supply of taxable products and services is subject to value-added tax, while the sale of luxury items is subject to sales tax. The practical applications of VAT and PPnBM are investigated in this study via the use of qualitative research methodologies. Based on the data, it seems that VAT and PPnBM change annually, with VAT generally going up and PPnBM generally going down. Important societal and economic consequences of VAT and PPnBM were also discovered by this study. State income may be increased by VAT, while societal tax expenses can be reduced through PPnBM. Observation, interviews, and the examination of relevant data are the means of data collection used in this descriptive analytic study. We anticipate that this study's findings will add to our understanding of VAT and PPnBM, as well as the ways in which these policies might affect our country's economy and way of life.